College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.1 - Functions - 2.1 Exercises: 19

Answer

$f(-3)=3$ $f(3)=3$ $f(0)=-6$ $f( \frac{1}{2})=-\frac{23}{4}$

Work Step by Step

We are given: $f(x)=x^{2}-6$ We evaluate: $f(-3)=(-3)^{2}-6=9-6=3$ $f(3)=3^{2}-6=9-6=3$ $f(0)=0^{2}-6=-6$ $f( \frac{1}{2})=(\frac{1}{2})^{2}-6=\frac{1}{4}-6=\frac{1}{4}-\frac{6*4}{4}=-\frac{23}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.